Optimization of Distillation Process for Scale-up Production of Lavender Essential Oil: A Literature Review - Dwipa, Yusri Hajjo; Salsabila, Cheryl; ‘Azmi, Madah Ikrimatul; Sukmawati, Nani; Assyifa, Muhammad Zaky; Syauqillah, Ahmad; Fikroh, Retno Aliyatul (Universitas Pendidikan Mandalika, 2024)
Lavender essential oil being one of the most used essential oils. Oxygenated monoterpenes are the largest constituent of lavender essential oil and the determinant of the characteristic aroma produced. Lavender flowers are composed of several ingredients, such as essential oils, alpha-pinene, beta-myrcene, limonene, cineol, linalool, terpinine-4-ol, and linalyl acetate. The aim of this study is to develop an efficient, effective, and profitable method of lavender oil extraction that can be used for commercial scale production, in order to determine which method is most suitable for scale-up production. The method used in this study is literature review with the results of literature reviews conducted, the method with the highest percentage of essential oil components is the use of innovative methods such as extraction with the help of microwaves (MW) with the percentage of linalool (32.90%) linaly acetate (27%), extraction with the help of ultrasonic (AS) with the percentage of linalool (37.6% ), linalyl acetate (18.4%)., supercritical fluid extraction (SF) with linalool (24%), extraction, and negative pressure extraction (NPCE) with linalool percentage (27.18%) linaly acetate (25.23%). While the smallest percentage of essential oil components in the use of molecular distillation is the percentage of Linalool (4.56%), linaly acetate (12.78%). The originality of this research contribution can open the door for further research and wider practical applications.